2013
DOI: 10.3109/13625187.2013.774358
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study examining short-term changes in bone mineral density among class 3 obese users of depot-medroxyprogesterone acetate

Abstract: DMPA-SC administration affects L-spine bone health similarly regardless of BMI status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…When a number of cardiometabolic risk markers measured at baseline and at 18 weeks were compared across BMI groups, no differences were noted except for the Disposition Index, a measure of β-cell compensation for insulin resistance, which decreased in obese women (− 286) and increased in nonobese women (188.5) (p = .04) [14]. Finally, small decreases in mean bone mineral density (BMD) at the lumbar spine measured by Dual Energy X-ray Absorbtiometry (DEXA) were noted at 18 weeks postenrolment among all DMPA-SC-users (normal: − 0.083, obese: − 0.091. extremely obese: − 0.112, p = .89), though no difference was reported across BMI groups [15]. All participants had normal BMD at baseline.…”
Section: Other Adverse Effectsmentioning
confidence: 80%
See 4 more Smart Citations
“…When a number of cardiometabolic risk markers measured at baseline and at 18 weeks were compared across BMI groups, no differences were noted except for the Disposition Index, a measure of β-cell compensation for insulin resistance, which decreased in obese women (− 286) and increased in nonobese women (188.5) (p = .04) [14]. Finally, small decreases in mean bone mineral density (BMD) at the lumbar spine measured by Dual Energy X-ray Absorbtiometry (DEXA) were noted at 18 weeks postenrolment among all DMPA-SC-users (normal: − 0.083, obese: − 0.091. extremely obese: − 0.112, p = .89), though no difference was reported across BMI groups [15]. All participants had normal BMD at baseline.…”
Section: Other Adverse Effectsmentioning
confidence: 80%
“…Of the 296 articles identified by the search strategy, 14 satisfied the review inclusion criteria. Twelve articles presented results for seven studies investigating DMPA-SC use among women with four conditions or characteristics identified in the WHO MEC, including obesity [5,[9][10][11][12][13][14][15], age [9][10][11] endometriosis [16][17][18] and HIV [19]. Four of these articles report on results from three multinational pivotal Phase 3 contraceptive trials, including results from two noncomparative trials of DMPA-SC users conducted at sites in North and South America, Europe, and Asia, and a randomized, evaluatorblinded trial comparing DMPA-SC and DMPA-IM users conducted in the United States, Canada, and Brazil [5,[9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations